Glycogen storage diseases with liver involvement: a literature review of GSD type 0, IV, VI, IX and XI - Miriam Massese; Francesco Tagliaferri; Carlo Dionisi-Vici; Arianna Maiorana (Orphanet Journal of Rare Diseases, 2022)
Abstract Background Glycogen storage diseases (GSDs) with liver involvement are classified into types 0, I, III, IV, VI, IX and XI, depending on the affected enzyme. Hypoglycemia and hepatomegaly are hallmarks of disease, but muscular and renal tubular involvement, dyslipidemia and osteopenia can develop. Considering the paucity of literature available, herein we provide a narrative review of these latter forms of GSDs. Main body Diagnosis is based on clinical manifestations and laboratory test results, but molecular analysis is often necessary to distinguish the various forms, whose presentation can be similar. Compared to GSD type I and III, which are characterized by a more severe impact on metabolic and glycemic homeostasis, GSD type 0, VI, IX and XI are usually known to be responsive to the nutritional treatment for achieving a balanced metabolic homeostasis in the pediatric age. However, some patients can exhibit a more severe phenotype and an important progression of the liver and muscular disease. The effects of dietary adjustments in GSD type IV are encouraging, but data are limited. Conclusions Early diagnosis allows a good metabolic control, with improvement of quality of life and prognosis, therefore we underline the importance of building a proper knowledge among physicians about these rare conditions. Regular monitoring is necessary to restrain disease progression and complications.